2019
DOI: 10.1002/rrq.261
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Lagged Relations Among Linguistic Skills in European Portuguese: A Longitudinal Study

Abstract: Research has widely demonstrated the contribution of word reading, listening comprehension skills, and oral reading fluency to reading comprehension performance. However, the existence of reciprocal relations among these skills has been investigated less frequently. The authors examined the directionality of the relations among reading comprehension, listening comprehension, word reading, and oral reading fluency in Portuguese elementary school students from second to fourth grade by using a longitudinal cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 74 publications
(168 reference statements)
2
14
2
Order By: Relevance
“…According to the verbal efficiency theory (Perfetti, 1985), good reading fluency skills facilitate reading comprehension because automaticity in decoding reduces the resource demands of cognitive processes (e.g., memory and attention), which can then be allocated to comprehension. The strength of the relationship between reading fluency and reading comprehension diminishes over time (Florit and Cain, 2011;Torppa et al, 2016;Santos et al, 2019) as children become "fluent enough". This finding is in accordance with the Simple View of Reading (SVR) model (Gough and Tunmer, 1986;Hoover and Gough, 1990), which states that reading comprehension is a product of two separable abilities -decoding and linguistic comprehension.…”
Section: Reading Fluency and Reading Comprehension Difficultiesmentioning
confidence: 99%
“…According to the verbal efficiency theory (Perfetti, 1985), good reading fluency skills facilitate reading comprehension because automaticity in decoding reduces the resource demands of cognitive processes (e.g., memory and attention), which can then be allocated to comprehension. The strength of the relationship between reading fluency and reading comprehension diminishes over time (Florit and Cain, 2011;Torppa et al, 2016;Santos et al, 2019) as children become "fluent enough". This finding is in accordance with the Simple View of Reading (SVR) model (Gough and Tunmer, 1986;Hoover and Gough, 1990), which states that reading comprehension is a product of two separable abilities -decoding and linguistic comprehension.…”
Section: Reading Fluency and Reading Comprehension Difficultiesmentioning
confidence: 99%
“…Our data support the SVR model also in learners of transparent orthography, specifying that the word recognition component has to contemplate a measure of reading fluency, intended as rate of reading, together with reading accuracy. Findings are consistent with results obtained both in transparent (e.i., Tilstra et al, 2009;Protopapas et al, 2012), intermediate orthographies (such as French, i.e., Massonnié et al, 2019; European Portuguese, i.e., Cadime et al, 2017;Santos et al, 2020) and opaque orthographies (e.g., Joshi and Aaron, 2000;Kershaw and Schatschneider, 2012;Silverman et al, 2013) that support the necessity to add a fluency component to the SVR. After all, fluent reading is the result of a number of processes, that interact each other, and that need be curried out efficiently and automatically (Breznitz, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The SVR model has been widely tested in readers of English, a highly opaque orthography, but also in readers of intermediate orthographies (such as French, i.e., Massonnié et al, 2019 ; European Portuguese, i.e., Cadime et al, 2017 ; Santos et al, 2020 ; see also Sparks and Patton, 2016 for Spanish L2 learners and Buil-Legaz et al, 2016 for Spanish-Catalan bilingual children with language deficits) as well as more transparent alphabetic scripts such as Finnish (e.g., Torppa et al, 2016 ), Greek (e.g., Protopapas et al, 2012 , 2013 ; Kendeou et al, 2013 ) and Italian (e.g., Roch and Levorato, 2009 ; Tobia and Bonifacci, 2015 ). Evidence is also available for readers of some non-alphabetic writing systems, such as Chinese and Arabic (e.g., Joshi et al, 2012 ; Yeung et al, 2016 ; Asadi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have explored the empirical and theoretical links between oral reading fluency and reading competence (see, e.g., Eason, Sabatini, Goldberg, Bruce, & Cutting, 2013; García & Cain, 2014; Kim, Wagner, & Foster, 2011; Kim, Wagner, & Lopez, 2012; Silverman, Speece, Harring, & Ritchey, 2013; Tilstra, McMaster, Van den Broek, Kendeou, & Rapp, 2009). Research has suggested that in more transparent orthographies such as Creole, oral reading fluency plays an even larger role in reading comprehension than in reading accuracy (Cadime et al, 2017; Padeliadu & Antoniou, 2014; Santos, Cadime, Viana, & Ribeiro, 2019; Seguin, 2018). When students are able to read words with accuracy and speed, cognitive constraints are lifted, “allowing cognitive resources (e.g., working memory, attention) to be used for higher order meaning construction” (Kim, 2015, p. 460) that is needed for reading comprehension.…”
Section: Discussionmentioning
confidence: 99%